Konflik Sosial dalam novel Terusir karya Hamka - Fadhlurrahman, Muhammad Fauzi; Hayati, Yenni (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to describe: (1) the form of social conflict in the novel Terusir by Hamka,(2) the causes of social conflict in the novel Terusir by Hamka,(3) the impact of social conflict in the novel Terusir by Hamka. The object used in this research is the novel Terusir by Hamka, the first printed edition published by Gema Insani in 2016. The type of research used is literary research using descriptive methods. The data in this research are in the form of words, phrases, clauses and sentences that describe social conflict in the form of the narrator's narration about the characters, the characters' speeches, the characters' actions depicted in the setting of the novel Terusir by Hamka. The data collection techniques in this research are reading and understanding the novel, identifying the main character, recording data related to the research problem, and inventorying the data into an inventory format related to the novel Terusir by Hamka. Data analysis techniques include identifying and classifying data, interpreting data, concluding the results of data analysis, and reporting the results of data analysis in the form of a thesis. Based on data analysis, the following forms of social conflict were found in the novel Terusir by Hamka, namely (1) ersonal conflict, (2) group or family conflict, (3)conflict in society. The causes of social conflict are, (1) differences between individuals, (2) differences in social class, (3) differences in interests, (4) social change. The impact of social conflict is in the form of, (1) destruction of group unity, (2) changes in social personality, (3) destruction of norms and social values.